Functionality before and after physiotherapy in post COVID-19 patients: Funcionalidad antes y después de fisioterapia en pacientes post COVID-19 - López Siete, Margarita (2023)
Background: COVID-19 is a disease that since its appearance in 2019 has represented a challenge for health services. The sequelae are a consequence of a deterioration in the quality of life, fatigue, dyspnea and joint pain. Objective: Compare physical, respiratory, cognitive and functional independence functional parameters in post-COVID-19 patients, with respiratory sequelae before and after a respiratory physical and occupational therapy program. Methods: A comparative, quasi-experimental, prospective study was conducted in outpatients discharged from hospitalization due to COVID-19 in a 3rd level hospital of the Instituto Mexicano del Seguro Social in Puebla, Mexico during 2020-2021. Scales were applied before and after the rehabilitation program. Descriptive statistics were used. Results: We included 116 patients, 57.7% men, mean age 47.32 years (min. 20, max. 79); 77 (66.3%) patients had moderate symptoms in hospitalization. A significant p value was obtained (p <0.000) Conclusions: Significant improvement is observed in post-COVID-19 patients after receiving respiratory physical and occupational therapy.